2018
DOI: 10.3389/fimmu.2018.00201
|View full text |Cite
|
Sign up to set email alerts
|

Proximity of Cytomegalovirus-Specific CD8+ T Cells to Replicative Senescence in Human Immunodeficiency Virus-Infected Individuals

Abstract: Antiretroviral therapy (ART) effectively extends the life expectancy of human immunodeficiency virus (HIV)-infected individuals; however, age-related morbidities have emerged as major clinical concerns. In this context, coinfection with cytomegalovirus (CMV) accelerates immune senescence and elevates risk for other age-related morbidities, possibly through increased inflammation. We investigated potential relationships between CMV memory inflation, immune senescence, and inflammation by measuring markers of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…HeLa cells are a high telomere content control, and telomere length of HeLa cells was controlled by freshly thawing aliquots from the same passage number on the day of each experiment. After fixation, cells were resuspended in 250 µL PBS with 1% FBS and treated with chemical cross-linker bissulfosuccinimidyl suberate at a final concentration of 5 mM on ice for 30 minutes per a previously published protocol ( 29 ). The reaction was quenched with a 20-minute incubation in quenching solution (PBS with 100 mM Tris-HCl, 50 mM NaCl).…”
Section: Methodsmentioning
confidence: 99%
“…HeLa cells are a high telomere content control, and telomere length of HeLa cells was controlled by freshly thawing aliquots from the same passage number on the day of each experiment. After fixation, cells were resuspended in 250 µL PBS with 1% FBS and treated with chemical cross-linker bissulfosuccinimidyl suberate at a final concentration of 5 mM on ice for 30 minutes per a previously published protocol ( 29 ). The reaction was quenched with a 20-minute incubation in quenching solution (PBS with 100 mM Tris-HCl, 50 mM NaCl).…”
Section: Methodsmentioning
confidence: 99%
“…A recent study found coinfection with CMV was clearly associated with immunosenescence, but not with inflammation in PLWH [96]. Most studies have found an association between coinfection with CMV and increased inflammation [70,[97][98][99] and a large study reported increased risk for non-AIDS related clinical events with CMV coinfection [100].…”
Section: Hiv-associated "Premature" Aging and CMV Co-infectionmentioning
confidence: 99%
“…Expression of similar traits to those observed in senescent fibroblasts by Hayflick et al suggests that CMV-specific T cells could be a peri-senescent immune cell subset. A study of lymphocyte telomere length in HIV-infected individuals positioned CMV-specific CD8 + T cells as having the shortest telomeres and highest rate of telomere attrition [70]. Therefore, the accumulation of such immune cells through extensive proliferation could underlie a relationship between CMV infection and age-associated morbidity.…”
Section: Cytomegalovirus Infection Generates a Unique Cd8 + T-cell Sumentioning
confidence: 99%
See 1 more Smart Citation
“…Valid data on the effect of CMV infection on CRP levels are scarce. The available evidence shows an effect of CMV infection on CRP levels in HIV-negative patients and HIV-positive individuals with and without ART [ 35 , 36 ]. Concerning sCD163, previously published results of comparable cohorts showed higher concentrations of sCD163 in PLWH under long term ART and undetectable HIV RNA levels compared to age matched HIV-seronegative controls, but none of them was controlled for CMV serostatus [ 5 , 6 , 11 ].…”
Section: Discussionmentioning
confidence: 99%